2020
DOI: 10.1007/s10943-020-01063-y
|View full text |Cite
|
Sign up to set email alerts
|

Religious Cliché and Stigma: A Brief Response to Overlooked Barriers in COVID-19 Management

Abstract: For decades, religion has provided explanations and answers to existential questions and queries that can emerge during a pandemic. This characteristic of religion has helped communities in finding answers and meanings to their confusions. During a pandemic, healthcare professionals are often unprepared in answering the patients' religious beliefs regarding the diseases. Moreover, patients are faced with religious clichés and stigma that results because of religious beliefs and practices. To overcome the relig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
42
0
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 45 publications
(45 citation statements)
references
References 4 publications
1
42
0
2
Order By: Relevance
“…Positive religious strategies may be used with other psychological techniques to improve resilience and well-being among the affected populations; therefore, the role of religious leaders should be a part of healthcare team in dealing with this pandemic, and their influence should be utilized to raise awareness and change negative attitudes and practices among community members (Hashmi et al 2020 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Positive religious strategies may be used with other psychological techniques to improve resilience and well-being among the affected populations; therefore, the role of religious leaders should be a part of healthcare team in dealing with this pandemic, and their influence should be utilized to raise awareness and change negative attitudes and practices among community members (Hashmi et al 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, the results showed that positive religious coping was related to higher levels of psychological well-being and lower levels of depression (Ahrens et al 2010 ). In another study, Hashmi et al ( 2020 ) found that negative religious cliché and stigma related to COVID-19 in some Islamic developing countries have resulted in avoiding the established precautionary measures against the disease.…”
Section: Theoretical Backgroundmentioning
confidence: 99%
“…Another predictor of the stigma that we included in this study was religiosity, although no statistical association with CDRSDCHCW was found. The influence of religiosity on COVID-19 management, especially in developing countries, may generate certain practices that are deleterious to established precautionary measures against the disease; furthermore, the belief that life and death are controlled by the “Almighty”, which is also configured as a religious stigma that may impact precautionary measures against COVID-19 (Hashmi et al, 2020). This observation suggests that the relationship between stigma and religiosity is more complex and may be mediated by other types of variables not explored in this study.…”
Section: Discussionmentioning
confidence: 99%
“…A group of muslims avoid the recommended preventive action by refering to Quran; "Allah is sufficient to us; and he is the extraordinary guardian" (The Noble Quran, 2016b) [9]. Similarly, in India, in the name of the sacred and hereditary tradition, Hindu-nationalists, the supporters of the political parties of Prime Minister, Narendra Modi rollicking, perform a ritual of drinking the urine of a cow to prevent Covid-19.…”
Section: Mediatization Of Religionmentioning
confidence: 99%
“…Religion can provide meaning and promote human survival [8]. In common sense, people agree that religion can substantially contribute to promote health education and preventive actions against Covid-19 [9]. However, social reality proves that religious groups perform the hardest resistence against the policies related to Covid-19.…”
Section: Introductionmentioning
confidence: 99%